2020
DOI: 10.1155/2020/1621394
|View full text |Cite
|
Sign up to set email alerts
|

Exosome and Melatonin Additively Attenuates Inflammation by Transferring miR-34a, miR-124, and miR-135b

Abstract: The positive effects of mesenchymal stem cells (MSCs) are primarily activated through molecular secretions known as paracrine activity, which regulates the function of various cell types including immune cells. Accumulating evidence shows that exosomes of soluble factors released from MSCs are potential alternative agents for stem cell-based therapy, although the exact underlying mechanism has not been elucidated. The purpose of this study was to evaluate the potential effects of exosomes produced by adipose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Under other circumstances, such as lipopolysaccharide-induced Alzheimer's disease in rat neonates, melatonin decreases the pathological complications via the autophagy-SIRT-1 pathway and down-regulation of multiple miRNAs including miR-34a, -146a, and -126 (Meng et al, 2014;Carloni et al, 2016). Similarly, Heo et al (2020) showed that melatonin-stimulated exosomes isolated from adiposederived mesenchymal stem cells suppressed inflammation. These exosomes were enriched with multiple miRNAs such as miR-34a, -124, and -135b compared to non-treated melatonin exosomes.…”
Section: Effect Of Melatonin On Exosome Cargo Sortingmentioning
confidence: 98%
“…Under other circumstances, such as lipopolysaccharide-induced Alzheimer's disease in rat neonates, melatonin decreases the pathological complications via the autophagy-SIRT-1 pathway and down-regulation of multiple miRNAs including miR-34a, -146a, and -126 (Meng et al, 2014;Carloni et al, 2016). Similarly, Heo et al (2020) showed that melatonin-stimulated exosomes isolated from adiposederived mesenchymal stem cells suppressed inflammation. These exosomes were enriched with multiple miRNAs such as miR-34a, -124, and -135b compared to non-treated melatonin exosomes.…”
Section: Effect Of Melatonin On Exosome Cargo Sortingmentioning
confidence: 98%
“…Exosomes obtained from LPS preconditioning BMSCs can strongly increase M2 macrophage polarization and attenuated the postinfarction inflammation in a mouse MI model through inhibition of the LPSdependent NF-κB signaling pathway and activation of the AKT1/AKT2 signaling pathway [92]. Melatonin-stimulated exosomes derived from AD-MSCs can promote M2 macrophage differentiation and exerted superior anti-inflammatory modulation through miRNAs miR-34a, miR-124, and miR-135b [93]. Besides, several in vitro studies have also confirmed the immunosuppression and anti-inflammatory action of MSC-derived exosomes like miR-10a (facilitating Th17 and Treg responses) [94] and IDO (promoting the transformation of mononuclear cells to Tregs) [95].…”
Section: Limited Inflammationmentioning
confidence: 99%
“…Also, in order to assess the potential effects of exosomes released by adipose tissue MSCs on inflammatory modulation, Heo et al (94) examined the changes in anti-inflammatory genes, along with the polarization of M2 macrophages in fibroblasts treated with pro-inflammatory cytokines and THP-1 cells. They observed that exosome treatment positively regulated the expression of anti-inflammatory mRNA associated with M2 macrophages, in an inflammatory environment treated with gamma interferon and tumor necrosis factor alpha.…”
Section: Exosome-melatonin Therapy May Control the Inflammatory Process Associated With Colitis And Obesity And Assist In Wound Healingmentioning
confidence: 99%